Late‐Stage Isotopic Carbon Labeling of Pharmaceutically Relevant Cyclic Ureas Directly from CO2. Issue 31 (3rd July 2018) - Del Vecchio, Antonio; Caillé, Fabien; Chevalier, Arnaud; Loreau, Olivier; Horkka, Kaisa; Halldin, Christer; Schou, Magnus; Camus, Nathalie; Kessler, Pascal; Kuhnast, Bertrand; Taran, Frédéric; Audisio, Davide
Abstract: A robust, click‐chemistry‐inspired procedure for radiolabeling of cyclic ureas was developed. This protocol, suitable for all carbon isotopes ( 11 C, 13 C, 14 C), is based on the direct functionalization of carbon dioxide: the universal building block for carbon radiolabeling. The strategy is operationally simple and reproducible in different radiochemistry centers, exhibits remarkably wide substrate scope with short reaction times, and demonstrates superior reactivity as compared to previously reported systems. With this procedure, a variety of pharmaceuticals and an unprotected peptide were labeled with high radiochemical efficiency. Abstract : Label with a click : A Staudinger/aza‐Wittig approach to carbon labeling inspired by click chemistry has been developed that is suitable for all carbon isotopes ( 11 C, 13 C, 14 C). Thus, a variety of pharmaceuticals and an unprotected peptide were labeled with high radiochemical efficiency by urea formation between o ‐azidoanilines and isotopically labeled carbon dioxide (see picture).